What Could Derail the India Express? Economists Speak Out - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
For the investors and businesses still swooning over India's red-hot growth, a pair of economists delivered a splash of cold water to their faces on February 23 during a talk organized by the University of Pennsylvania's Center for the Advanced Study of India.